CHARACTERISTICS OF MAGNETIC SUSCEPTIBILITY IN THE DEPTH OF 100 ~ 2000M MAINHOLE OF CHINESE CONTINENTAL SCIENTIFIC DRILLING AND ITS GEOLOGICAL IMPLICATIONS - Yang T.; Liu Q.S.; Pan H.P.; Wu Y.; Jin Z.M.; Niu Y.X. (My University, 2006)
The characteristics of magnetic susceptibility of core samples and logging susceptibility from the depth of 100 ~ 2000m mainhole of Chinese Continental Scientific Drilling (CCSD) are systematically compared. The results indicate that lithology and retrograded metamorphic process are the main factors controlling susceptibility of rocks. Susceptibility of rocks with different lithology in their decreasing order are serpentinized garnet peridotite, orthogneiss, retrograded eclogite, eclogite, paragneiss and amphibolite. Marked differences in susceptibility of eclogite with different retrograded degree were observed. Due to the formation of magnetite and ilmenite during the retrograded process, the susceptibility of the moderately to strongly retrograded eclogite is the largest. However, that of the totally retrograded eclogite is the smallest resulting from the decomposition of the magnetite and ilmenite with the further retrograded effects, and the susceptibility of the fresh eclogite is intervenient. The ratio between susceptibility of core samples (κcore) and logging susceptibility (κlog) keep steady value within the depth of 100 ~ 2000m, Most of κcore/κlog are lower than 4.0, which accounts for about 70%, and the values lower than 2.0 are preponderant. With the increasing depth, there is no obvious variation in κcore/κlog of rocks with same lithology, such as eclogite, retrograded eclogite and paragneiss. In addition, the Euclid distance between κcore and κlog range from 3.0 to 6.4, no evident variations with depth. At the depth range of 100 ~ 600m the Euclid distance changes from 3.0 to 5.2, while at the depth range of 1500 ~ 2000m, it changes from 3.2 to 5.3. The Euclid distance range both at depth ranges of 100 ~ 600m and 1500 ~ 2000m are similar, showing that the susceptibility measured on core samples and at the logging approximate have the same variational characteristics in the whole borehole. Susceptibility of core samples was measured in laboratory with normal temperature and pressure, on the contrary, logging susceptibility was measured in-situ, under the real state in borehole, where the borehole pressure increases with the depth, but the ratios and Euclid distances between κcore and κlog keep steady variations with depth, suggesting that the variations of logging susceptibility are similar with that of the susceptibility of core samples, therefore the pressure in borehole has no effect on the susceptibility of rocks. The effects of pressure on magnetic susceptibility of rocks from depth of 100 ~ 2000m can be neglected when the logging susceptibility is used to interpret the magnetic anomalies in Sulu area. These results are helpful to obtain the in-situ magnetic parameters and to interpret the nature of magnetic anomalies in this area.
Keywords: CHINESE CONTINENTAL SCIENTIFIC DRILLING (CCSD); DONGHAI; LOGGING SUSCEPTIBILITY; PRESSURE; SUSCEPTIBILITY MEASURED ON CORE SAMPLES